Forage species introduction and evaluation on Elyonurus grassland in the Nhecolândia subregion in the Brazilian Pantanal - Comastri Filho, José Anibal; Pott, Arnildo (Pesquisa Agropecuaria Brasileira, 1994)
Agronomic evaluation on 173 grass and/or legume forages was performed, aiming selection of species adapted to ecologic conditions of Elyonurus grasslands in the Brazilian Pantanal. Forages were grown on two 1.5 x 3.0 m plots, one fertilized (F) and one unfertilized (U). Chemical fertilization improved vigor of plantlets of most species. An evaluation index (EI) ranging from 0 to 3 indicated that the most promising forages were Brachiaria humidicola (EI = 2.80), on both F and U plots, and Calopogonium mucunoides (EI = 2.65 on F plot and EI = 2.50 on U plot). B. humidicola had the best soil cover. Root nodules were found on legumes, despite lack of inoculation. Disease attacks were observed sporadically, especially during the rainy season. Most forages flowered from March to June.
Keywords: grasses; legumes; production; nodulation; drought tolerance; flood tolerance; pest resistance; disease resistance; soil cover; persistence